Study of antidiabetic activity of Aegle marmelos in streptozotocin-induced hyperglycemic Wistar rats in a tertiary care hospital - Chandra, Shruti; Prajapat, Rajeev; Bhosle, Deepak; Jaybhaye, Deepali (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Diabetes has become a major metabolic disorder disease that is increasingly becoming a killer disease worldwide. The aim of this study was to evaluate (bael tree) Aegle marmelos whole plant extract has the potential efficiency to control hyperglycemia, that affects kidney and lipid profile, in streptozotocin induced rats. This study aimed to evaluate the Antidiabetic activity of, Aegle marmelos in streptozotocin-induced hyperglycemic Wistar rats. Methods: Wistar rats of either sex were used grouped into six groups of six rats each. The first group was used as control, the second group was induced diabetes by inducting streptozotocin 70 mg/kg i.p., The 3rd,4th, 5th and 6th group was induced diabetes and treated with Metformin 600 mg/kg, A. marmelos methanol whole plant extract in the increasing dosage of 100 mg/kg, 200 mg/kg and 400 mg/kg body weight from the 7th to 28th day respectively. The blood samples were collected at day 0,7 and 28th day for estimation of fasting blood sugar, serum cholesterol, triglycerides and creatinine. Results was presented as the mean standard deviation (SD). A one-way analysis variance was performed using SPSS-17 and Graphpad Prism 5 statistical software. Results: After administration of Aegle marmelos extract in increasing level, fasting glucose level was significantly (p < 0.05) reduced. Also, there is significant reduction in serum cholesterol level, triglyceride level and creatinine level. The effect was more after 28 days of treatment. Conclusions: The study results indicate the active compounds in the Aegle marmelos whole plant methanol extract has antidiabetic and antilipidemic activity. It can also protect kidney to some extent.